Shaping healthy and sustainable food systems with behavioural food policy. (22nd June 2021) - Reisch, Lucia A
Abstract: This paper focuses on policies that are enlightened by behavioural insights (BIs), taking decision-makers' biases and use of heuristics into account and utilising a people-centric perspective and full acknowledgement of context dependency. Considering both the environmental and pandemic crises, it sketches the goal of resilient food systems and describes the contours of behavioural food policy. Conceptually built on BIs derived from behavioural economics, consumer research and decision science, such an approach systematically uses behavioural policies where appropriate and most cost-effective. BI informed tools (nudges) can be employed as stand-alone instruments (such as defaults) or used to improve the effectiveness of traditional policy tools.